Laws regulating brandishing, firing, carrying, & concealed carrying of firearms, Title 11, § 385, § 386 in The Revised Statutes of Arizona Territory (1901) - (:unkn) unknown (General Publisher, 1901)
Prohibited the carry on the person, or in saddlebags, of any pistol, dirk, dagger, slung-shot, sword-cane, spear, brass knuckles, Bowie-knife, or any other kind of knife manufactured for purposes of offense or defense.
--
Keywords: CARRY